COMPARATIVE REVIEW OF METHODOLOGIES FOR ESTIMATING THE COST OF ADVERSE DRUG REACTIONS IN THE RUSSIAN FEDERATION AND BRAZIL - G. I. Syraeva; A. S. Kolbin; A. V. Matveev; V. S. Panezhina (Фармация и фармакология (Пятигорск))
The aim of the review article was to highlight the methodologies for assessing the financial costs of adverse drug reactions exemplified by the Russian Federation and Brazil.Materials and methods: for a comparative analysis, materials from open sources were used. The study of the experience of methods used for assessing the burden of adverse drug reactions, was carried out using the system for calculating payments for medical care by clinical-statistical and clinical-profile groups, the methodology for assessing the severity of adverse events of the US National Cancer Institute, drug-associated problems, and “the decision tree” model.Results. When comparing the costs of ADR management in the Russian Federation and Brazil, the following results have been obtained: in the Russian Federation, the “cost” of reaction can be estimated only for a limited number of nosological groups that are regulated by the classification of diseases by clinical and statistical groups; in Brazil, when predicting the costs of adverse reactions management, the combination of “the decision tree” method and the Delphi method is used. In the Russian Federation, the cost of the 3rd and above severity adverse event (according to CTCAE v. 4.03), varies from 26,849.22 up to 26,196.37 RUB in the North-West region (St. Petersburg). In Brazil, the cost of ADR ranges from 13 USD (the best scenario for the patient) to 574 USD (the worst scenario for the patient), which is about 975 and 43,000 RUB, respectively. The introduction of methods that make it possible to predict the development and potential outcomes of adverse drug reactions, as well as taking into account the experiences of foreign colleagues in their modeling, will reduce economic costs in the Russian Federation at the federal level.Conclusion: for the economic value analysis and further forecasting, an improvement of existing methodologies is required. The models used in the Russian Federation (“the decision tree”, classification of diseases by clinical groups, Markov model) do not take into account the time factor, therefore, when planning the analysis of potential costs for adverse reactions, it is necessary to reinforce the methods with such tools as QALY, YLL, and YLD.